In Search of a Harrowing Tale: Manuscripts of the Latin Translation of 'De Christi passione' (Interfaces: A Journal of Medieval European Literatures, 2024)
This paper examines the manuscripts of the Latin translation of Eusebius of Alexandria's sermo 17 as evidence for medieval text searches. This homily, which treats the apprehension of Jesus, his trial and subsequent descent into hell, is found in four manuscripts (Oxford, Bodleian Library, Bodley 343; Cambridge, St John’s College, C. 12; München, Bayerische Staatsbibliothek, Clm14540; Salzburg, Stiftsbibliothek St Peter, a VII 5), which evince two distinct searches for the homily. In the English manuscripts, the homily fills a lacuna in Easter season within the Homiliary of Angers. In the earlier two manuscripts, the homily appears as part of a textual block that served to stock developing library collections. The evidence these manuscripts present for text-hunting help elucidate the influence the work of this obscure Byzantine author had in the Latin world.
Keywords: Eusebius of Alexandria; De passione Domini; Homiliary of Angers; Salzburg; St Emmeram